Hubungan Dukungan Keluarga dalam Kepatuhan Pengobatan Pasien TB Paru Terhadap Pencegahan TB MDR Pasien Rawat Jalan di Rumah Sakit - Fajar, Dwi; Silaen, Harsudianto (Infomasi dan Promosi Kesehatan, 2022)
Family support is an activity oriented towards improving family function based on raising children and other family activities in a system and supporting resources. Client compliance is behavior towards the provisions given by health workers. MDR TB is a condition in which the bacteria are resistant to OAT. TB-resistant TB is the result of the treatment of TB patients who are not regularly infected or infected by TB-resistant TB patients. This study aims to identify the relationship between family support in medication adherence in pulmonary TB patients and the prevention of MDR TB in outpatients. The research method used is a quantitative research using a correlation design. The sample consisted of 73 outpatient pulmonary TB patients. Participation in this study using Systematic Random Sampling. Researchers collected data using family support research instruments using a questionnaire. MDR TB prevention adherence used a standardized questionnaire based on the MMAS-8 adherence questionnaire. The statistical test uses the Spearman Rank statistical test. treatment of TB patients with prevention of MDR TB has a value of r = 0.962, which means that there is a significant or very strong influence between family support in the treatment of TB patients on the prevention of MDR TB in patients at Aminah Hospital, Tangerang City in 2021. Conclusion Family support influences the treatment of TB patients against prevention of MDR TB